2015
DOI: 10.3906/biy-1409-60
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitory activity of hydroxycapsaicin, a synthetic derivative of capsaicin, and its cytotoxic effects against human colon cancer cell lines

Abstract: Capsaicin possesses cytotoxic/anticancer activity and shares some common structural features, including a benzene ring and a long hydrophobic carbon tail, with the histone deacetylase (HDAC) inhibitors trichostatin A and suberoylanilide hydroxamic acid. The aims of this study were to investigate HDAC inhibitory and cytotoxic activities of a synthetic derivative of capsaicin, hydroxycapsaicin (6-hydroxy-N-(4-hydroxy-3-methoxybenzyl)-8-methylnonenamide), in colon cancer cell lines. Hydroxycapsaicin inhibited HDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…The MTT reduction assay was performed with non-cancer (Vero), human cervical cancer (HeLa), human lung carcinoma (A549) and human breast adenocarcinoma cancer (MCF-7) cell lines according to the method previously described [ 33 , 34 , 35 ]. Briefly, cells were seeded in a 96-well plate and incubated for 24 h. The cells were treated with the selected compounds and incubated at 37 °C in CO 2 for 24 h, 48 h, and 72 h. After incubation, the culture medium was exchanged with 110 μL of MTT (0.5 mg/mL in PBS medium) and incubated for 2 h. The amount of MTT formazan product was determined after dissolved in DMSO by measuring its absorbance with a microplate reader (Bio-Rad Laboratories, USA) at a test wavelength of 550 nm and a reference wavelength of 655 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The MTT reduction assay was performed with non-cancer (Vero), human cervical cancer (HeLa), human lung carcinoma (A549) and human breast adenocarcinoma cancer (MCF-7) cell lines according to the method previously described [ 33 , 34 , 35 ]. Briefly, cells were seeded in a 96-well plate and incubated for 24 h. The cells were treated with the selected compounds and incubated at 37 °C in CO 2 for 24 h, 48 h, and 72 h. After incubation, the culture medium was exchanged with 110 μL of MTT (0.5 mg/mL in PBS medium) and incubated for 2 h. The amount of MTT formazan product was determined after dissolved in DMSO by measuring its absorbance with a microplate reader (Bio-Rad Laboratories, USA) at a test wavelength of 550 nm and a reference wavelength of 655 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Lee, Krisanapun, and Baek (2010) reported that capsaicin inhibited the growth of human lung cancer and colorectal cancer cells by up‐regulating the NAG‐1 gene expression and binding of C/EBP β with glycogen synthase kinase 3 β (GSK3 β ), and thus activated the transcription factor 3 (ATF3) and helped in inhibition of the GSK3 β and Protein Kinase C pathways. Capsaicin and its derivative hydroxycapsaicin were observed for potential cytotoxic histone deacetylase inhibitory activity by inducing S‐phase cell cycle arrest in both HT29 and HCT116 colon cancer cells (Senawong, Wongphakham, Saiwichai, Phaosiri, & Kumboonma, 2015). The carotenoids namely capsanthin, capsanthin 3′‐ester, capsanthin 3,3′‐diester, capsorubin, capsorbin diester, capsanthin 3,6‐epoxide, and cucurbitaxanthin A‐3′ester exhibited significant in vitro antitumor activity on Epstein–Barr virus early antigen (EBV‐EA) activation induced by 12‐ O ‐tetradecanoylphorbol‐13‐acetate (TPA) as a tumor promoter.…”
Section: Pharmacological Activities Of C Annuum and Its Active Consti...mentioning
confidence: 99%
“…reported that capsaicin inhibited the growth of human lung cancer and colorectal cancer cells by up-regulating the NAG-1 gene expression and binding of C/EBPβ with glycogen synthase kinase 3β (GSK3β), and thus activated the transcription factor 3 (ATF3) and helped in inhibition of the GSK3β and Protein Kinase C pathways. Capsaicin and its derivative hydroxycapsaicin were observed for potential cytotoxic histone deacetylase inhibitory activity by inducing S-phase cell cycle arrest in both HT29 and HCT116 colon cancer cells(Senawong, Wongphakham, Saiwichai, Phaosiri, & Kumboonma, 2015). The carotenoids namely capsanthin, capsanthin 3 0 -ester, capsanthin 3,3 0 -diester, capsorubin, capsorbin diester, capsanthin 3,6-epoxide, and cucurbitaxanthin A-3 0 ester exhibited significant in vitro antitumor activity on Epstein-Barr virus early antigen (EBV-EA) activation induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) as a tumor promoter.Out of that carotenoids namely capsanthin, capsanthin 3 0 -ester, and capsanthin 3,3 0 -diester exhibited potent in vivo antitumor-promoting activity by mouse skin two-stage carcinogenesis assay through 7,12-dimethylbenz[α]anthracene as an initiator and TPA as a promoter(Maoka, Mochida, et al, 2001).The anticancer potentials of C. annuum and capsaicin are summarized in Figure 7.…”
mentioning
confidence: 99%
“…Its highest cytotoxicity activity was exerted against p53 knockout HCT116 cell line (IC50: 19.67 µM), indicating these types of cells to be more sensitive to capsaicin than their corresponding p53 wild type HCT116 cells. A study by Senawong et al [ 25 ] demonstrated the anti-proliferative activity of capsaicin without cell-cycle arrest property against HCT 116 cells. Furthermore, it was shown that pepper seed extract, at a concentration of 500 µg/ml, exhibited greater anti-proliferative activity (96.8%) and increased apoptotic cell population by 2.2-fold in HCT 116 cell line [ 26 ].…”
Section: Main Textmentioning
confidence: 99%